Profil Minat Siswa SMA Kelas XII untuk Menjadi Calon Pendidik Biologi Di Era Gen-Z - Helfita, Rani; Nursal, Nursal; Zulfarina, Zulfarina (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the profile of interest of high school students in grade XII to become prospective biology educators in the Gen-Z era. The method used in this study is a descriptive method. To achieve this goal, a study has been conducted using a descriptive research design with a quantitative approach. The population of this study was taken from two schools, namely SMA Negeri 8 Pekanbaru totaling 454 students consisting of 12 classes and SMA Negeri 15 Pekanbaru totaling 241 students consisting of 7 classes. The number of samples was taken using the Purposive Sampling technique. The instruments used were questionnaires and interview sheets. Data were obtained by distributing questionnaires, as well as interviews, then the data obtained were analyzed descriptively. the results of the study on the profile of interest of high school students in grade XII to become prospective biology educators in the Gen-Z era were obtained from the analysis of each indicator, namely cognition (knowing) was in the interested category with a percentage of 84%, emotion (feeling) was in the less interested category with a percentage of 73%, and conation (will) was in the less interested category with a percentage of 58%. Meanwhile, in students of SMA Negeri 15 Pekanbaru, it was obtained from each indicator, namely cognition (knowing) was in the interested category with a percentage of 85%, emotion (feeling) was in the less interested category with a percentage of 74%, and conation (will) was in the less interested category with a percentage of 65%. The conclusion of this study is that students of SMA Negeri 15 Pekanbaru are 1% more interested in becoming prospective biology educators than students of SMA Negeri 8 Pekanbaru.